An S-O-R Framework for B2B Logistics Provider Selection Decisions: The Moderating Role of Switching Costs - Bùi, Văn Hùng; Phạm, Thái Hoàng; Bùi, Công Sơn (Journal of Transportation Science and Technology, 2026)
This study establishes an integrated analytical framework underpinned by the S-O-R model, Dynamic Capabilities Theory, and Switching Cost Theory to elucidate the impact mechanism of dynamic technological capabilities on the selection of logistics service providers (LSPs) within a business-to-business (B2B) context. The central thesis posits that dynamic technological capability functions as a strategic stimulus (S) that shapes the internal cognitive states of organizational clients, encompassing perceived value and trust at the primary processing level, and corporate image perception at the cumulative cognitive level (O), subsequently driving their service usage decision-making behaviors (R). Notably, the research clarifies the positive moderating role of switching costs on two internal cognitive relationships within the Organism component: the effect of perceived value on corporate image and the effect of trust on corporate image, grounded in the cognitive dissonance reduction mechanism. The expected findings aim to contribute to the theoretical foundation of organizational buying behavior and offer critical managerial implications for logistics service providers in the digital era
Keywords: Logistics service provider selection; S-O-R framework; Switching costs; Dynamic technological capability; Organizational buying behavior